When Prime Brokers Fail : the Unheeded Risk to Hedge Funds, Banks, and the Financial Industry - Aikman, J. S. (Bloomberg, 2010)
Praise for When Prime Brokers Fail. "An essential guide to understanding why so many hedge funds failed during the 2008 crash and why so many will continue to fail in the future.". Franois Lhabitant, PhD Chief Investment Officer, Kedge Capital Professor of Finance, EDHEC Business School. "A must-read for every hedge fund manager, investment banking executive, and prime brokerage professional. This is hands down the most educational resource on the challenges, trends, and risks within the prime brokerage space.". Richard Wilson, founder of the Prime Brokerage Associat.